Analisis Pembelajaran Matematika Di SMK Adi Luhur Dan SMK Nusantara Wisata Respati Pada Kurikulum Merdeka Dan Kurikulum Revisi 2018 - Adib Rozan; Sri Hastuti Rhomawati; Melati br Pasaribu (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by the implementation of the independent vocational school curriculum in the Jakarta area, especially East Jakarta, which has begun to be implemented in the 2022/2020 academic year. Teachers and students in this case still do not have an understanding and readiness regarding the system for implementing the independent curriculum in the learning process, because they are still influenced by The learning system in the 2013 curriculum has not been fully implemented well in schools, causing teachers and students to be overwhelmed in preparing and adapting to be able to carry out learning activities well. The aim of the research is to determine Mathematics and Student learning in the Implementation of the Merdeka Vocational School Curriculum in East Jakarta. This type of research is descriptive research with a qualitative approach. This research was carried out at 2 vocational schools in East Jakarta with a total of 5 teachers as research informants. Data collection techniques through interviews and documentation. Based on the research results, it shows that the teachers' interviews show that students do not understand how to use the 2018 revised curriculum and the Merdeka curriculum itself.